Wear behavior of bionic impregnated diamond bits. (February 2016) - Wang, Zhaozhi; Zhang, Zhihui; Sun, Youhong; Gao, Ke; Liang, Yunhong; Li, Xiujuan; Ren, Luquan
Abstract: Bionic impregnated diamond samples with self-regenerated non-smooth surface were designed and fabricated based on bionic theory. The surface was characterized by several concave units that continuously kept their shape and function during whole service process. Abrasive ratio tests were carried out to investigate its performance. Results showed that bionic samples possess a superior wear resistance and grinding performance. The particle trapping effect reduced the wear of metal matrix, played an important role in improving the performance of bionic impregnated diamond bits. Microscopic imaging and analysis were applied to observed and reveal the effect of self-regenerated units on the wear behavior.